Anti-ultraviolet / salt-spray-resistant polyamide composite material and preparation method thereof

By introducing modified UV-resistant salts and polydopamine-modified hydrotalcite nanoparticles into the polyamide materials, the problem of aging of polyamide materials in ultraviolet and salt spray environments is solved, and the material's stable UV-resistant and salt spray resistance is achieved, and the service life is extended.

CN119823571AActive Publication Date: 2025-04-15GOODALL MATERIALS TECHNOLOGY (CHUZHOU) CO LTD

Patent Information

Application Number
CN202510049586.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-15
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

Polyamide materials are prone to aging in ultraviolet rays and salt spray environments, resulting in a decrease in mechanical properties and shortened service life. The interface bond between existing anti-ultraviolet agents and polyamide matrix is ​​unstable, affecting material performance.

Method used

UV-resistant/salt spray-resistant polyamide composite materials are used, which include polyamide resin, modified UV-resistant salt and polydopamine-modified hydrotalcite nanoparticles. By combining the modified UV-resistant salt and polyamide masterbatch and the addition of polydopamine-modified hydrotalcite nanoparticles, the material's UV-resistant and salt spray-resistant properties are improved.

Benefits of technology

The long-lasting, stable UV resistance and salt spray resistance of polyamide composite materials are achieved, the mechanical properties of the material are maintained, and the service life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005239575550000131
    Figure BDA0005239575550000131
  • Figure BDA0005239575550000141
    Figure BDA0005239575550000141
Patent Text Reader

Abstract

The invention discloses an anti-ultraviolet / salt-spray-resistant polyamide composite material and a preparation method thereof, and relates to the field of engineering plastic processing. The anti-ultraviolet polyamide composite material comprises the following components in parts by mass: 70-94 parts of polyamide resin, 5-20 parts of anti-ultraviolet polyamide master batch and 1-10 parts of polydopamine modified hydrotalcite nanoparticles, the anti-ultraviolet polyamide master batch is prepared from the following components in parts by mass: 55 to 99 parts of polyhexamethylene adipamide salt solution with the mass concentration of 5 to 50 percent, 1 to 50 parts of modified anti-ultraviolet agent salt and 0.3 to 1.5 parts of antioxidant; the modified anti-ultraviolet agent salt is obtained by reacting 5-50 parts of an amino-terminated modified anti-ultraviolet agent compound and 5-50 parts of dicarboxylic acid in absolute ethyl alcohol; the polydopamine modified hydrotalcite nano-particles comprise layered hydrotalcite nano-particles and a polydopamine coating layer on the surfaces of the layered hydrotalcite nano-particles. The anti-ultraviolet / salt-fog-resistant polyamide composite material has lasting and stable anti-ultraviolet performance and salt-fog-resistant performance, meanwhile, the excellent mechanical performance of the polyamide material can be kept, and the anti-ultraviolet / salt-fog-resistant polyamide composite material has high application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal conductive materials, and in particular to an anti-ultraviolet / salt fog resistant polyamide composite material and a preparation method thereof. Background Art

[0002] Polyamide (nylon) materials have good comprehensive properties, including mechanical properties, heat resistance, wear resistance, chemical resistance, self-lubrication and easy processing characteristics, and are widely used in defense, machinery, chemical industry and other fields. However, polyamide materials will age under sunlight, ultraviolet rays or high-energy radiation, and will have defects such as yellowing, brittleness, cracking, surface loss of gloss, and deterioration of mechanical and electrical properties, which will eventually lose their use value. In addition, there are a large number of polar amide groups in polyamide. In high humidity and salt spray environments, water molecules and salt substances can easily penetrate and cause the resin matrix to absorb moisture, swell, plasticize, and corrode, resulting in changes such as decreased mechanical properties, reduced dimensional stability, surface damage and molecular degradation of the material, making the material ineffective and reducing its service life.

[0003] Adding ultraviolet absorbers to polyamide material products is currently the main method to delay ultraviolet aging and extend the service life. For example, in patent 202410307632.6, rare earth oxides with good anti-ultraviolet properties are modified by cardanol, and long carbon chain groups are grafted on the surface of rare earth oxides by the complexation of its phenolic hydroxyl group with rare earth elements, which improves the dispersibility of rare earth oxides and their compatibility with nylon matrix, and prepares nylon materials with good anti-ultraviolet properties; patent 202011431131.7 introduces anti-ultraviolet agent nano titanium dioxide in the polymerization process of caprolactam to prepare anti-ultraviolet nylon masterbatch, which is further compounded with special nylon materials to obtain anti-ultraviolet biaxially stretched nylon film. However, due to the small particle size, large specific surface area and low polarity of the anti-ultraviolet agent particles, the interface bonding between the anti-ultraviolet agent and the polyamide matrix is ​​not stable enough, and the agglomerated anti-ultraviolet agent particles will also deteriorate the performance of polyamide. Therefore, it is urgent to find a substance or method that can combine the anti-ultraviolet agent with the polyamide matrix more stably and evenly. Summary of the invention

[0004] In order to solve the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide an anti-ultraviolet / salt spray resistant polyamide composite material and a preparation method thereof. The anti-ultraviolet / salt spray resistant polyamide composite material of the present invention has durable and stable anti-ultraviolet performance and salt spray resistance, and has high application value.

[0005] The present invention provides the following technical solutions:

[0006] The present invention provides an anti-ultraviolet / salt spray resistant polyamide composite material, which comprises the following components in parts by mass: 70 to 94 parts of polyamide resin, 5 to 20 parts of anti-ultraviolet polyamide masterbatch and 1 to 10 parts of polydopamine modified hydrotalcite nanoparticles;

[0007] The anti-ultraviolet polyamide masterbatch comprises the following components in parts by weight: 55-99 parts of a polyhexamethylene adipamide salt solution with a mass concentration of 5-50%, 1-50 parts of a modified anti-ultraviolet agent salt and 0.3-1.5 parts of an antioxidant; the modified anti-ultraviolet agent salt is obtained by reacting 5-50 parts of an amino-terminated modified anti-ultraviolet agent compound and 5-50 parts of a dicarboxylic acid in anhydrous ethanol;

[0008] The polydopamine-modified hydrotalcite nanoparticles include layered hydrotalcite nanoparticles and a polydopamine coating layer on the surface thereof.

[0009] Furthermore, the modified UV inhibitor salt is obtained by dissolving an amino-terminated modified UV inhibitor compound and a dicarboxylic acid in anhydrous ethanol, reacting the mixture in a water bath at 50 to 80° C. for 1 to 3 hours, and finally filtering, washing, and purifying the mixture.

[0010] Furthermore, the amino-terminated modified UV inhibitor compound comprises the following components in parts by mass: 5 to 40 parts of UV inhibitor A, 2 to 80 parts of multifunctional isocyanate compound, 10 to 70 parts of modifier, 5 to 10 parts of UV inhibitor B, 1 to 50 parts of diamine, 60 to 100 parts of acetone and 0.01 to 5 parts of catalyst.

[0011] Furthermore, the amino-terminated modified UV inhibitor compound is prepared by the following method: UV inhibitor A, multifunctional isocyanate compound and catalyst are uniformly dispersed in a solvent, heated to 40-70° C. under a protective atmosphere and reacted for 2-3 hours; then, the modifier and UV inhibitor B are added and reacted at 70-90° C. for 2-3 hours; finally, diamine is added and the reaction is continued at 60-100° C. for 0.5-1 hour to obtain the amino-terminated modified UV inhibitor compound.

[0012] Preferably, the anti-ultraviolet agent A is selected from at least one of 4,4'-dihydroxybenzophenone, 2,4-dihydroxybenzophenone, 3,4-dihydroxybenzophenone, 2,2'-dihydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-hydroxy-4-methoxybenzophenone and ethylene glycol salicylate.

[0013] Preferably, the anti-ultraviolet agent B is selected from at least one of PEG functionalized nano-silicon dioxide, propylene glycol nano-titanium dioxide, amino titanium dioxide nanoparticles, amino silicon dioxide nanoparticles, and amino zinc oxide nanoparticles.

[0014] Preferably, the diamine is selected from at least one of ethylenediamine, propylenediamine, hexamethylenediamine, 1,4-butanediamine, 1,5-pentanediamine and 1,6-hexamethylenediamine.

[0015] Preferably, the modifier is selected from at least one of polyethylene glycol, polypropylene glycol, 2,2-dihydroxymethylbutyric acid, 2,2-dihydroxymethylpropionic acid, 3,5-dihydroxy-3-methylvaleric acid, and 4,5-dihydroxy-2-(hydroxymethyl)valeric acid.

[0016] Preferably, the molecular weight of the polyethylene glycol is 400-8000 g / mol; the molecular weight of the polypropylene glycol is 400-2000 g / mol.

[0017] Preferably, the molar ratio of the multifunctional isocyanate compound, the UV-resistant agent A, the modifier and the diamine is (2.5-3):1:1:(0.6-1.2).

[0018] Furthermore, by compounding the anti-ultraviolet agent A, the polyfunctional isocyanate compound, the anti-ultraviolet agent B and the diamine, the hydroxyl group of the anti-ultraviolet agent A, the amino group and the diamine of the anti-ultraviolet agent B can react with the polyfunctional isocyanate compound, thereby obtaining an amino-terminated modified anti-ultraviolet agent through molecular structure modification.

[0019] Preferably, the solvent is selected from any one of acetone, ether, glacial acetic acid, methanol, isopropanol and ethyl acetate.

[0020] Preferably, the catalyst is selected from any one of dibutyltin, tributyltin, tributyltincyclopentadienyl, triethylenediamine, dibutyltin dilaurate, dibutyltin diacetate, triethanolamine, and dimethylaminoimidazole.

[0021] Preferably, the dicarboxylic acid is selected from at least one of oxalic acid, adipic acid, azelaic acid, sebacic acid, terephthalic acid and isophthalic acid.

[0022] Preferably, the molar ratio of the amino-terminated modified UV inhibitor compound to the dicarboxylic acid is 1:1.

[0023] Preferably, the antioxidant is selected from at least one of 2,6-di-tert-butyl-4-methylphenol, 2,6-di-tert-butyl-4-(dimethylaminomethyl)phenol, 4,4'-methylenebis(2,6-di-tert-butylphenol), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite, tris[2,4-di-tert-butylphenyl]phosphite, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylbenzyl)propionate.

[0024] Preferably, the multifunctional isocyanate compound is at least one selected from toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate.

[0025] Furthermore, the polydopamine modified hydrotalcite nanoparticles are obtained by reacting 5 to 20 parts by mass of dopamine hydrochloride and 1 to 10 parts by mass of layered hydrotalcite nanoparticles in a buffer solution with a pH of 8.3-8.7; the buffer solution is a tris(hydroxymethyl)aminomethane solution with a mass concentration of 2 to 20%. Preferably, the reaction is specifically: stirring the reaction at 30 to 50°C for 5 to 8 hours.

[0026] Furthermore, the polyamide resin is selected from one of polycaprolactam (PA6) resin, polydecanoic acid (PA10) resin, polyundecalactam (PA11) resin, polydodecalactam (PA12) resin, polybutylene adipamide (PA46) resin, polypentamethylene adipamide (PA56) resin, PA66 (polyhexamethylene adipamide) resin, polyhexamethylene sebacamide (PA610) resin, polyhexamethylene dodecanediamide (PA612) resin, polydecanediamide (PA1010) resin, polydecanediamide (PA1012) resin, and polydodecanediamide (PA1212) resin.

[0027] The present invention also provides a method for preparing the above-mentioned UV-resistant / salt-fog-resistant polyamide composite material, comprising the following steps:

[0028] S1. preparing a modified anti-ultraviolet agent salt; dissolving an amino-terminated modified anti-ultraviolet agent compound and a dicarboxylic acid in anhydrous ethanol, reacting the mixture in a water bath at 50 to 80° C. for 1 to 3 hours, filtering, washing and purifying to obtain a modified anti-ultraviolet agent salt;

[0029] S2, preparing UV-resistant polyamide masterbatch; adding modified UV-resistant agent salt to polyhexamethylene adipamide salt solution, and reacting under pressure at 200-230° C. and 2-3 MPa for 0.5-2 h; after reducing the pressure to normal pressure, adding antioxidant, and then reacting under -0.3-0.1 MPa and 260-290° C. for 0.5-1 h to obtain UV-resistant polyamide masterbatch;

[0030] S3, the polyamide resin, the anti-ultraviolet polyamide masterbatch and the polydopamine-modified hydrotalcite nanoparticles are mixed evenly and then extruded, and pelletized and dried to obtain the anti-ultraviolet / salt spray resistant polyamide composite material.

[0031] Furthermore, in the step S3, the polyamide resin, the anti-ultraviolet polyamide masterbatch and the polydopamine-modified hydrotalcite nanoparticles are evenly mixed and extruded in a twin-screw extruder, the temperature of the feeding section of the twin-screw extruder is 140-185°C, the temperature of the other sections and the die is 190-260°C; the screw speed is 150-280r / min.

[0032] Through the above scheme design, the present invention has the following effects:

[0033] The anti-ultraviolet / salt spray resistant polyamide composite material prepared by the invention has more durable and stable anti-ultraviolet performance and salt spray resistance performance, and can maintain the excellent mechanical properties of the polyamide material itself.

[0034] The anti-ultraviolet agent salt is obtained by reacting an amino-terminated modified anti-ultraviolet agent compound with a dicarboxylic acid, and then the anti-ultraviolet agent salt is compounded with a polyhexamethylene adipamide salt and an antioxidant, so that the chemical bonds of the anti-ultraviolet agent are connected to the molecular chain of the polyamide masterbatch to form a highly dispersed anti-ultraviolet polyamide masterbatch, thereby improving its compatibility with the polyamide resin, effectively solving the phase separation in the process of blending the traditional anti-ultraviolet agent with the polyamide, and improving the anti-ultraviolet aging performance of the polyamide;

[0035] By utilizing the high efficiency barrier property of layered hydrotalcite particles against salt spray and the strong adhesion characteristics of polydopamine, the polydopamine-modified hydrotalcite nanoparticles can construct a strong interfacial interaction with the polyamide resin, exert its high efficiency salt spray barrier effect, reduce the plasticization and corrosion problems caused by the penetration of water molecules and salt substances into the polyamide resin, and extend its service life under salt spray conditions. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0038] It should also be understood that the terms used in this specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the specification of the present invention and the appended claims, the singular forms "a", "an" and "the" are intended to include plural forms unless the context clearly indicates otherwise.

[0039] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0040] In addition, the terms "roughly" and "basically" are intended to explain that the relevant content does not require absolute precision, but can have certain deviations. For example, "roughly equal" does not only mean absolute equality. Since it is difficult to achieve absolute "equality" in actual production and operation, there are generally certain deviations. Therefore, in addition to absolute equality, "roughly equal" also includes the above-mentioned situation with certain deviations. Taking this as an example, in other cases, unless otherwise specified, the terms "roughly" and "basically" have similar meanings to the above.

[0041] Example 1

[0042] An anti-ultraviolet / salt spray resistant polyamide composite material is prepared by the following method:

[0043] S1. Evenly disperse 5 parts of anti-ultraviolet agent A, 10 parts of toluene diisocyanate and 0.1 parts of dibutyltin dilaurate in 60 parts of acetone, and heat to 40°C for reaction for 2 hours under nitrogen protection; then, add 20 parts of polyethylene glycol (molecular weight 1000 g / mol) and 5 parts of amino-treated titanium dioxide nanoparticles and react at 70°C for 2 hours; further add 1 part of propylene diamine and continue to react at 60°C for 0.5 hours to obtain an amino-terminated modified anti-ultraviolet agent compound; wherein, the anti-ultraviolet agent A includes 3 parts of 4,4'-dihydroxybenzophenone and 2 parts of 2,2'-dihydroxy-4-methoxybenzophenone.

[0044] S2, dissolving 20 parts of amino-terminated modified UV inhibitor compound and 10 parts of malonic acid in 100 parts of anhydrous ethanol, reacting in a water bath at 50° C. for 1 hour, and obtaining a modified UV inhibitor salt after filtering, washing and purification;

[0045] S3, dissolving 15 parts of polyhexamethylene adipamide salt in 85 parts of ionized water to prepare a polyhexamethylene adipamide salt solution with a mass concentration of 15%; then adding 20 parts of modified anti-ultraviolet agent salt to 100 parts of the polyhexamethylene adipamide salt solution, and reacting at 200°C and 2MPa in a reactor for 0.5h; then, adjusting the pressure relief valve, releasing the pressure of the reactor to normal pressure, adding 0.3 parts of 2,6-di-tert-butyl-4-methylphenol to the reactor, closing the pressure relief valve, starting the vacuum pump, and when the pressure in the reactor is -0.3MPa, reacting at 260°C for 0.5h to obtain anti-ultraviolet polyamide masterbatch;

[0046] S4, dissolving 5 parts of tris(hydroxymethyl)aminomethane in 95 parts of deionized water, and adjusting the pH value of the solution to 8.5 with hydrochloric acid to obtain a buffer solution. Then, adding 5 parts of dopamine hydrochloride and 2 parts of layered hydrotalcite nanoparticles to the buffer solution, stirring and reacting at 30°C for 5 hours. The obtained hydrotalcite nanoparticles were washed with deionized water until neutral, and dried until constant weight, to obtain polydopamine-modified hydrotalcite nanoparticles;

[0047] S5. After uniformly mixing 94 parts of PA1010 resin, 20 parts of anti-ultraviolet polyamide masterbatch, and 2 parts of polydopamine-modified hydrotalcite nanoparticles, the mixture was extruded through a twin-screw extruder (the temperature of the feeding section was 140°C, and the screw speed was 150 r / min). After pelletizing and drying, an anti-ultraviolet / salt spray resistant polyamide composite material was obtained.

[0048] Example 2

[0049] A method for preparing an anti-ultraviolet / salt spray resistant polyamide composite material is prepared by the following method:

[0050] S1. 18 parts of 2,2'-dihydroxy-4-methoxybenzophenone, 33 parts of a multifunctional isocyanate compound, and 0.5 parts of dibutyltin diacetate are uniformly dispersed in 80 parts of ether, and heated to 50°C under nitrogen protection to react for 2.5 hours; then, 28 parts of polypropylene glycol (molecular weight 600 g / mol) and 6 parts of amino-treated silica nanoparticles are added to react at 80°C for 2.5 hours; further, 5 parts of hexamethylenediamine are added to continue the reaction at 75°C for 0.6 hours to obtain an amino-terminated modified UV inhibitor compound; wherein the multifunctional isocyanate compound includes isophorone diisocyanate and hexamethylene diisocyanate in a mass ratio of 1:2.

[0051] S2, dissolving 20 parts of the amino-terminated modified UV inhibitor compound and 25 parts of adipic acid in 100 parts of anhydrous ethanol, reacting in a water bath at 60° C. for 1.2 hours, and then filtering, washing and purifying to obtain a modified UV inhibitor salt;

[0052] S3, dissolving 34 parts of polyhexamethylene adipamide salt in 66 parts of ionized water to prepare a 34% polyhexamethylene adipamide salt solution; then adding 39 parts of modified anti-ultraviolet agent salt to the polyhexamethylene adipamide salt solution, and reacting in a reactor at 220° C. and 2.5 MPa for 1 hour; then, adjusting the pressure relief valve, releasing the pressure in the reactor to normal pressure, adding 0.5 parts of 2,6-di-tert-butyl-4-(dimethylaminomethyl)phenol to the reactor, closing the pressure relief valve, starting the vacuum pump, and when the pressure in the reactor is -0.2 MPa, reacting at 270° C. for 0.8 hours to obtain anti-ultraviolet polyamide masterbatch;

[0053] S4, dissolving 12 parts of tris(hydroxymethyl)aminomethane in 88 parts of deionized water, and adjusting the pH value of the solution to 8.5 with hydrochloric acid to obtain a buffer solution. Then, adding 10 parts of dopamine hydrochloride and 5 parts of layered hydrotalcite nanoparticles to the buffer solution, stirring and reacting at 40°C for 6 hours. The obtained hydrotalcite nanoparticles were washed with deionized water until neutral, and dried until constant weight, to obtain polydopamine-modified hydrotalcite nanoparticles;

[0054] S5. 85 parts of PA66 resin, 15 parts of anti-ultraviolet polyamide masterbatch, and 3 parts of polydopamine-modified hydrotalcite nanoparticles are uniformly mixed, and then extruded through a twin-screw extruder (the feeding section temperature is 155°C, and the screw speed is 200r / min). After pelletizing and drying, an anti-ultraviolet / salt spray resistant polyamide composite material is obtained.

[0055] Example 3

[0056] A method for preparing an anti-ultraviolet / salt spray resistant polyamide composite material is prepared by the following method:

[0057] S1. Disperse 28 parts of 2,2',4,4'-tetrahydroxybenzophenone, 72 parts of dicyclohexylmethane diisocyanate and 1.0 part of triethanolamine uniformly in 90 parts of glacial acetic acid, and heat to 70°C for reaction for 2.2 hours under nitrogen protection; then, add 17 parts of 2,2-dihydroxymethylbutyric acid and 7 parts of anti-ultraviolet agent B and react at 90°C for 2.3 hours; further add 6 parts of 1,4-butylene diamine and continue to react at 90°C for 1 hour to obtain an amino-terminated modified anti-ultraviolet agent compound; wherein the anti-ultraviolet agent B comprises propylene glycol nano-titanium dioxide and amino-silica nanoparticles in a mass ratio of 1:1;

[0058] S2, dissolving 38 parts of amino-terminated modified UV inhibitor compound and 41 parts of dicarboxylic acid in 100 parts of anhydrous ethanol, reacting in a water bath at 80° C. for 2.4 hours, and then filtering, washing and purifying to obtain a modified UV inhibitor salt;

[0059] S3, dissolving 29 parts of polyhexamethylene adipamide salt in 71 parts of ionized water to prepare a 29% polyhexamethylene adipamide salt solution; then adding 33 parts of modified anti-ultraviolet agent salt to the polyhexamethylene adipamide salt solution, and reacting at 230°C and 3MPa in a reactor for 2 hours; then, adjusting the pressure relief valve, releasing the pressure in the reactor to normal pressure, adding 0.6 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate to the reactor, closing the pressure relief valve, starting the vacuum pump, and when the pressure in the reactor is -0.1MPa, reacting at 290°C for 1 hour to obtain an anti-ultraviolet polyamide masterbatch;

[0060] S4, dissolving 20 parts of tris(hydroxymethyl)aminomethane in 80 parts of deionized water, and adjusting the pH value of the solution to 8.5 with hydrochloric acid to obtain a buffer solution. Then, adding 20 parts of dopamine hydrochloride and 8 parts of layered hydrotalcite nanoparticles to the buffer solution, stirring and reacting at 50°C for 8 hours. The obtained hydrotalcite nanoparticles were washed with deionized water until neutral, and dried until constant weight, to obtain polydopamine-modified hydrotalcite nanoparticles;

[0061] S5. After uniformly mixing 90 parts of PA6 resin, 13 parts of anti-ultraviolet polyamide masterbatch, and 4 parts of polydopamine-modified hydrotalcite nanoparticles, the mixture was extruded through a twin-screw extruder (the temperature of the feeding section was 165°C, and the screw speed was 210 r / min). After pelletizing and drying, an anti-ultraviolet / salt spray resistant polyamide composite material was obtained.

[0062] Example 4

[0063] A method for preparing an anti-ultraviolet / salt spray resistant polyamide composite material is prepared by the following method:

[0064] S1. Disperse 40 parts of ethylene glycol salicylate, 80 parts of hexamethylene diisocyanate, and 5 parts of tributyltin uniformly in 95 parts of acetone, and heat to 55°C for reaction for 2 hours under nitrogen protection; then, add 70 parts of 4,5-dihydroxy-2-(hydroxymethyl)valeric acid and 7 parts of amino zinc oxide nanoparticles and react at 85°C for 2 hours; further add 50 parts of 1,4-butanediamine and continue to react at 80°C for 0.5 hours to obtain an amino-terminated modified UV inhibitor compound;

[0065] S2, dissolving 5 parts of amino-terminated modified UV inhibitor compound and 5 parts of sebacic acid in 100 parts of anhydrous ethanol, reacting in a water bath at 75° C. for 1.5 hours, and then filtering, washing and purifying to obtain a modified UV inhibitor salt;

[0066] S3, dissolving 50 parts of polyhexamethylene adipamide salt in 50 parts of ionized water to prepare a 50% polyhexamethylene adipamide salt solution; then adding 50 parts of modified anti-ultraviolet agent salt to the polyhexamethylene adipamide salt solution, and reacting at 200°C and 2MPa in a reactor for 1 hour; then, adjusting the pressure relief valve, releasing the pressure in the reactor to normal pressure, adding 1.5 parts of bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite to the reactor, closing the pressure relief valve, starting the vacuum pump, and when the pressure in the reactor is -0.2MPa, reacting at 270°C for 0.6h to obtain anti-ultraviolet polyamide masterbatch;

[0067] S4, dissolving 2 parts of tris(hydroxymethyl)aminomethane in 98 parts of deionized water, and adjusting the pH value of the solution to 8.7 with hydrochloric acid to obtain a buffer solution. Then, adding 5 parts of dopamine hydrochloride and 1 part of layered hydrotalcite nanoparticles to the buffer solution, stirring and reacting at 30°C for 7 hours. The obtained hydrotalcite nanoparticles were washed with deionized water until neutral, and dried until constant weight, to obtain polydopamine-modified hydrotalcite nanoparticles;

[0068] S5. Evenly mix 75 parts of PA46 resin, 20 parts of anti-ultraviolet polyamide masterbatch, and 10 parts of polydopamine-modified hydrotalcite nanoparticles, extrude through a twin-screw extruder (the temperature of the feeding section is 185°C, and the screw speed is 150 r / min), and obtain an anti-ultraviolet / salt spray resistant polyamide composite material after pelletizing and drying.

[0069] Example 5

[0070] A method for preparing an anti-ultraviolet / salt spray resistant polyamide composite material is prepared by the following method:

[0071] S1. Disperse 10 parts of ethylene glycol salicylate, 2 parts of toluene diisocyanate, and 0.35 parts of dimethylaminoimidazole uniformly in 100 parts of ethyl acetate, and heat to 40°C for reaction for 3 hours under nitrogen protection; then, add 5 parts of 2,2-dihydroxymethylbutyric acid, 5 parts of lysine diisocyanate, and 7 parts of anti-ultraviolet agent B and react at 75°C for 3 hours; further add 2 parts of 1,4-butanediamine and continue to react at 80°C for 0.7 hours to obtain an amino-terminated modified anti-ultraviolet agent compound; wherein the anti-ultraviolet agent B comprises amino-terminated titanium dioxide nanoparticles and amino-terminated silicon dioxide nanoparticles in a mass ratio of 2:3;

[0072] S2, dissolving 50 parts of amino-terminated modified UV inhibitor compound and 50 parts of dicarboxylic acid in 100 parts of anhydrous ethanol, reacting in a water bath at 55° C. for 3 hours, and then filtering, washing and purifying to obtain a modified UV inhibitor salt;

[0073] S3, dissolving 5 parts of polyhexamethylene adipamide salt in 95 parts of ionized water to prepare a 5% polyhexamethylene adipamide salt solution; then adding 1 part of modified anti-ultraviolet agent salt to the polyhexamethylene adipamide salt solution, and reacting at 210°C and 3MPa in a reactor for 1.5 hours; then, adjusting the pressure relief valve, releasing the pressure in the reactor to normal pressure, adding 0.5 parts of triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylbenzyl) propionate to the reactor, closing the pressure relief valve, starting the vacuum pump, and when the pressure in the reactor is -0.1MPa, reacting at 280°C for 1 hour to obtain anti-ultraviolet polyamide masterbatch;

[0074] S4, dissolving 20 parts of tris(hydroxymethyl)aminomethane in 80 parts of deionized water, and adjusting the pH value of the solution to 8.3 with hydrochloric acid to obtain a buffer solution. Then, adding 15 parts of dopamine hydrochloride and 10 parts of layered hydrotalcite nanoparticles to the buffer solution, stirring and reacting at 50°C for 5 hours. The obtained hydrotalcite nanoparticles were washed with deionized water until neutral, and dried until constant weight, to obtain polydopamine-modified hydrotalcite nanoparticles;

[0075] S5. After uniformly mixing 94 parts of PA1010 resin, 5 parts of anti-ultraviolet polyamide masterbatch and 1 part of polydopamine-modified hydrotalcite nanoparticles, the mixture was extruded through a twin-screw extruder (the temperature of the feeding section was 140°C and the screw speed was 280 r / min). After pelletizing and drying, an anti-ultraviolet / salt spray resistant polyamide composite material was obtained.

[0076] Comparative Example 1

[0077] Compared with Example 1, the difference in Comparative Example 1 is that the added amount of propylenediamine is 0.5 parts, and the other components, preparation steps and parameters are the same.

[0078] Comparative Example 2

[0079] Compared with Example 2, Comparative Example 2 is different in that 2,2'-dihydroxy-4-methoxybenzophenone is used instead of the anti-ultraviolet polyamide masterbatch, and the other components, preparation steps and parameters are the same.

[0080] Comparative Example 3

[0081] Compared with Example 2, Comparative Example 3 is different in that amino-containing silica nanoparticles are used instead of UV-resistant polyamide masterbatch, and the other components, preparation steps and parameters are the same.

[0082] Comparative Example 4

[0083] Compared with Example 3, Comparative Example 4 is different in that no polydopamine-modified hydrotalcite nanoparticles are added, and the other components, preparation steps and parameters are the same.

[0084] Comparative Example 5

[0085] Compared with Example 3, Comparative Example 5 is different in that layered hydrotalcite nanoparticles are used to replace polydopamine-modified hydrotalcite nanoparticles, and the other components, preparation steps and parameters are the same.

[0086] Comparative Example 6

[0087] Compared with Example 3, Comparative Example 6 is different in that 18 parts of polydopamine-modified hydrotalcite nanoparticles are added, and the other components, preparation steps and parameters are the same.

[0088] To illustrate the technical effect of the present invention, the polyamide composite materials prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were melt-injected into strips, and their tensile strength was tested with reference to GB / T 1040.2-2022; their flexural strength was tested with reference to GB / T 9341-2008; and their notched impact strength was tested with reference to GB / T 1843-2008. The test results are shown in Table 1 below.

[0089] Table 1 Mechanical properties test results of polyamide composites

[0090] sample Tensile strength(MPa) Bending strength(MPa) <![CDATA[Impact strength (KJ / m 2 )]]> Example 1 92.23 161.21 22.49 Example 2 85.15 126.36 31.44 Example 3 75.89 105.34 24.68 Example 4 103.62 159.46 36.84 Example 5 90.72 162.59 23.05 Comparative Example 1 86.88 147.32 19.11 Comparative Example 2 79.44 115.12 27.80 Comparative Example 3 83.71 120.86 30.82 Comparative Example 4 67.78 80.52 19.77 Comparative Example 5 71.88 91.32 21.11 Comparative Example 6 55.72 60.59 17.38

[0091] As shown in Table 1, for Examples 1 to 5 of the present invention, due to the strong interfacial interaction between the anti-ultraviolet polyamide masterbatch and the polydopamine-modified hydrotalcite nanoparticles and the polyamide resin, the two are uniformly dispersed in the polyamide resin, effectively improving the mechanical properties of the polyamide composite material. For Comparative Example 1, the amount of diamine added is too small, so that the amino-terminated modified anti-ultraviolet agent compound cannot be generated, so it is difficult to obtain the anti-ultraviolet agent salt and the anti-ultraviolet polyamide masterbatch, which significantly affects the processing performance and mechanical properties of the polyamide composite material. For Comparative Example 2, the anti-ultraviolet agent is directly used to replace the anti-ultraviolet polyamide masterbatch for the preparation of the polyamide composite material, and its tensile strength and flexural strength are reduced. For Comparative Example 5, the layered hydrotalcite nanoparticles have a weak interaction with the polyamide resin matrix and are easy to agglomerate, resulting in a decrease in the tensile strength and flexural strength of the composite material; for Comparative Example 6, a large amount of polydopamine-modified hydrotalcite nanoparticles are difficult to disperse in the polyamide matrix, resulting in a significant decrease in the mechanical properties of the composite material.

[0092] To further illustrate the technical effect of the present invention, the UV-resistant / salt-fog-resistant polyamide composite materials of Examples 1 to 5 and Comparative Examples 1 to 6 were subjected to UV-resistant tests and salt-fog-resistant tests.

[0093] (1) Anti-ultraviolet test

[0094] The polyamide composite materials prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were melt-injected into strips, and the mechanical property retention and dimensional stability of the samples were tested after aging for 1000 hours under ultraviolet light according to the method of GB / T 16422.2-2022. The test results are shown in Table 2 below:

[0095] Table 2 Mechanical properties and dimensional change rate of polyamide composites after 1000h UV aging

[0096]

[0097] As shown in Table 2, it can be seen from Table 2 that for Examples 1 to 3, due to the good anti-ultraviolet aging properties of the anti-ultraviolet polyamide masterbatch, adding it to the polyamide matrix can significantly improve the anti-ultraviolet performance of the composite material. After 1000h of ultraviolet aging, its mechanical properties and dimensional changes are small. For Comparative Example 1, the anti-ultraviolet aging performance of the composite material is poor. After aging for 1000h in an ultraviolet environment, its mechanical properties and dimensional stability are significantly reduced. For Comparative Examples 2 and 3, 2,2'-dihydroxy-4-methoxybenzophenone and amino-silica nanoparticles are used instead of the anti-ultraviolet polyamide masterbatch, respectively. The mechanical properties of the polyamide composite material are reduced, the dimensional change rate is significantly increased, and the overall anti-ultraviolet aging performance is relatively low.

[0098] (2) Salt spray resistance test

[0099] The polyamide composite materials prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were melt-injected into specimens, and the mechanical property retention and dimensional stability of the samples were tested in a salt spray corrosion test chamber (LRHS-663-RY type) after aging for 1000 hours according to the method of GB / T 10125-2012. The test results are shown in Table 3 below:

[0100] Table 3 Mechanical properties and dimensional change rate of polyamide composites after 1000h salt spray aging

[0101]

[0102] As shown in Table 3, for Examples 1 to 5 and Comparative Examples 1 to 3, the polydopamine-modified hydrotalcite nanoparticles with high barrier properties can effectively reduce the penetration of water molecules and salt substances into the resin matrix and their plasticization and corrosion effects on the resin. After 1000 hours of salt spray aging, the mechanical properties of the polyamide composite material are still maintained at a high value, and the size change rate of the sample is small, showing good anti-salt spray aging performance. For Comparative Example 4, without adding polydopamine-modified hydrotalcite nanoparticles, after 1000 hours of salt spray aging, the mechanical properties of the polyamide composite material are significantly reduced, the size change rate of the sample increases, and the anti-salt spray aging performance is weak. For Comparative Example 5, the dispersibility of hydrotalcite nanoparticles in the polyamide matrix is ​​poor, which greatly reduces its salt spray aging resistance. For Comparative Example 6, a large amount of polydopamine-modified hydrotalcite nanoparticles are difficult to be evenly dispersed in the polyamide matrix. After long-term salt spray aging, the mechanical properties of the polyamide composite material are reduced, and the size change rate of the sample increases, showing low anti-salt spray aging performance.

[0103] In summary, the UV-resistant / salt-fog-resistant polyamide composite material of the present invention has good stability, has excellent UV resistance and salt-fog resistance under the premise of ensuring its mechanical properties, and its mechanical properties can still be maintained at a high value after 1000h UV aging or 1000h salt-fog aging, and its dimensional change rate is small. When the technical scheme of the present invention is changed, the stability of the final polyamide composite material will be negatively affected to varying degrees, making it impossible to take into account mechanical properties, UV resistance and salt-fog resistance.

[0104] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A UV-resistant / salt-fog-resistant polyamide composite material, characterized in that: The invention comprises the following components in parts by weight: 70 to 94 parts of polyamide resin, 5 to 20 parts of anti-ultraviolet polyamide masterbatch and 1 to 10 parts of polydopamine-modified hydrotalcite nanoparticles; The anti-ultraviolet polyamide masterbatch comprises the following components in parts by weight: 50 to 99 parts of a polyhexamethylene adipamide salt solution with a mass concentration of 5 to 50%, 1 to 50 parts of a modified anti-ultraviolet agent salt and 0.3 to 1.5 parts of an antioxidant; the modified anti-ultraviolet agent salt is obtained by reacting 5 to 50 parts of an amino-terminated modified anti-ultraviolet agent compound and 5 to 50 parts of a dicarboxylic acid in anhydrous ethanol; The polydopamine-modified hydrotalcite nanoparticles include layered hydrotalcite nanoparticles and a polydopamine coating layer on the surface thereof.

2. The UV-resistant / salt-fog-resistant polyamide composite material according to claim 1, characterized in that: The amino-terminated modified UV inhibitor compound comprises the following components in parts by mass: 5 to 40 parts of UV inhibitor A, 2 to 80 parts of multifunctional isocyanate compound, 10 to 70 parts of modifier, 5 to 10 parts of UV inhibitor B, 1 to 50 parts of diamine, 60 to 100 parts of solvent and 0.01 to 5 parts of catalyst.

3. The UV-resistant / salt-fog-resistant polyamide composite material according to claim 2, characterized in that: The amino-terminated modified UV inhibitor compound is prepared by the following method: UV inhibitor A, multifunctional isocyanate compound and catalyst are uniformly dispersed in a solvent, heated to 40-70°C under a protective atmosphere for reaction for 2-3 hours; then, a modifier and UV inhibitor B are added and reacted at 70-90°C for 2-3 hours; finally, a diamine is added and the reaction is continued at 60-100°C for 0.5-1 hour to obtain the amino-terminated modified UV inhibitor compound.

4. The UV-resistant / salt-fog-resistant polyamide composite material according to claim 2, characterized in that: The anti-ultraviolet agent A is selected from at least one of 4,4'-dihydroxybenzophenone, 2,4-dihydroxybenzophenone, 3,4-dihydroxybenzophenone, 2,2'-dihydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-hydroxy-4-methoxybenzophenone and ethylene glycol salicylate.

5. The UV-resistant / salt-fog-resistant polyamide composite material according to claim 2, characterized in that: The anti-ultraviolet agent B is selected from at least one of PEG functionalized nano-silicon dioxide, propylene glycol nano-titanium dioxide, amino titanium dioxide nanoparticles, amino silicon dioxide nanoparticles, and amino zinc oxide nanoparticles.

6. The UV-resistant / salt-fog-resistant polyamide composite material according to claim 2, characterized in that: The diamine is selected from at least one of ethylenediamine, propylenediamine, hexamethylenediamine, 1,4-butanediamine, 1,5-pentanediamine and 1,6-hexamethylenediamine.

7. The UV-resistant / salt-fog-resistant polyamide composite material according to claim 2, characterized in that: The modifier is selected from at least one of polyethylene glycol, polypropylene glycol, 2,2-dihydroxymethylbutyric acid, 2,2-dihydroxymethylpropionic acid, 3,5-dihydroxy-3-methylvaleric acid, and 4,5-dihydroxy-2-(hydroxymethyl)valeric acid.

8. The UV-resistant / salt-fog-resistant polyamide composite material according to claim 2, characterized in that: The catalyst is selected from any one of dibutyltin, tributyltin, tributyltin cyclopentadienyl, triethylenediamine, dibutyltin dilaurate, dibutyltin diacetate, triethanolamine and dimethylaminoimidazole.

9. The UV-resistant / salt-fog-resistant polyamide composite material according to any one of claims 1 to 8, characterized in that: The polydopamine modified hydrotalcite nanoparticles are obtained by reacting 5-20 parts by mass of dopamine hydrochloride and 1-10 parts by mass of layered hydrotalcite nanoparticles in a buffer solution with a pH of 8.3-8.7; the buffer solution is a tris(hydroxymethyl)aminomethane solution with a mass concentration of 2-20%.

10. A method for preparing an anti-ultraviolet / salt spray resistant polyamide composite material, characterized in that: The following steps are involved: S1, preparing modified UV-resistant salt; The amino-terminated modified UV inhibitor compound and dicarboxylic acid are dissolved in anhydrous ethanol, reacted in a water bath at 50 to 80° C. for 1 to 3 hours, filtered, washed and purified to obtain a modified UV inhibitor salt; S2, preparing UV-resistant polyamide masterbatch; adding modified UV-resistant agent salt to polyhexamethylene adipamide salt solution, and reacting under pressure at 200-230° C. and 2-3 MPa for 0.5-2 h; after reducing the pressure to normal pressure, adding antioxidant, and then reacting under -0.3-0.1 MPa and 260-290° C. for 0.5-1 h to obtain UV-resistant polyamide masterbatch; S3, the polyamide resin, the anti-ultraviolet polyamide masterbatch and the polydopamine-modified hydrotalcite nanoparticles are mixed evenly and then extruded, and pelletized and dried to obtain the anti-ultraviolet / salt spray resistant polyamide composite material.

Citation Information

Patent Citations

  • Anti-ultraviolet bi-oriented nylon film with straight tearing and preparation method thereof

    CN112590338A

  • Anti-ultraviolet nylon material based on cardanol modified rare earth oxide and preparation method of anti-ultraviolet nylon material

    CN118085554A

  • Preparation method and application of modified anti-corrosion super-hydrophobic integrated coating

    CN112300697A

  • Preparation method of nanofiltration membrane and nanofiltration membrane prepared by same

    CN117181020A

Cited By

  • Method for preparing packing belt by utilizing printing waste film

    CN122125879A

  • A method for preparing packing straps using waste printed film

    CN122125879B